Kinetics Study of Oxidation of Medroxyprogestrone in Presence Alkaline Potassium Permanganate - Momen Heravi, Mohammad; Adineh Mohammadzadeh, Massoumeh (Asian Journal of Chemistry, 2013)
Medroxyprogesterone is a progestin (a from of progesterone), a female hormone that helps regulate ovulation (the release of an ovule from ovary) and menstrual periods. Medroxyprogesterone is used to treat condition such as absent or irregular menstrual periods and abnormal uterine bleeding. Medroxyprogesteroneis also used to prevent overgrowth in the lining of the uterus in postmenopausal women who are receiving estrogen hormone replacement therapy. The rate of oxidation of this drug with alkaline potassium permanganate in aqueous solutions has been studied at five different temperature by UV-visible spectroscopic method. In this work, we estimated the value of reaction rate constants and reaction order at 25 ºC under pseudo-order rate kinetic model (R2 > 0.996). The activation energy has been calculated from plotted Ln k vs. 1/T at temperature ranges between 25º-45 ºC is 579. 26 J/K mol.